Experiencia sobre resolución de conflictos entre culturas a través de un aula-taller de Educación Intercultural - Araque Hontangas, Natividad (Revista Complutense de Educación, 2009)
Problem-solving in Intercultural Education make the process of understanding easier and help the student’s acquisition of Knowledge about the gypsy culture. This paper explains problem-solving about racism as a method of teaching. It poses three activitys on Multicultural Education and analyses the results.